FRI0407 USER-FRIENDLINESS OF A NOVEL DEDICATED KNEE JOINT DISTRACTION DEVICE: EXPERIENCES FROM CLINICAL PRACTICE. (2nd June 2020) - Jansen, M.; Struik, T.; Mastbergen, S.; Custers, R.
Abstract : Background: Knee joint distraction (KJD) is a validated surgical technique that aims to postpone arthroplasty for a prolonged time in younger knee osteoarthritis (OA) patients (<65 years). In absence of dedicated devices intended for KJD, this procedure has thus far been performed with general purpose external fixation devices. 1 The demonstrated clinical benefits of KJD raised a clinical demand for a dedicated device (DD), including a desire for increased user-friendliness and decreased treatment burden. As such, in a multi-disciplinary setting with clinicians, patients, and medical device experts, several desired device characteristics were determined. These included perpendicular positioning of bone pins relative to the longitudinal tibia axis, surgery time < 45 minutes, no protruding parts above the most proximal and below the most distal bone pins, and pin tracts that are accessible for pin tract care. Based on the desired characteristics, a dedicated distraction device was developed and made available for clinical application. Objectives: To compare user-friendliness between the developed DD and previously used concept device (CD) used in regular care. Methods: Patients were treated with either the CD (n=22) or DD (n=22) in clinical practice. For both devices, the surgical technique was identical: fixation to the tibia and femur with 8 bone pins (figure 1) and 5 mm distraction for 6 weeks. The intervention duration when placing the device (defined as time between first incision and the surgeon being finished) was registered for all patients. After treatment, patients were asked to fill out a custom questionnaire about user-friendliness of the device during treatment, consisting of 25 questions on difficulties performing activities regarding clothing, sleeping, device care, daily activities, movement and complications. Intervention duration was compared between groups using an independent t-test while for questionnaire answers Mann Whitney U tests were used. Chi-square tests were used when comparing (complication) occurrences between groups. Results: Intervention duration was on average shorter for the DD (44 vs 56 minutes; p<0.001). 34 Patients (16 CD, 18 DD) completed the questionnaire. Patient user-friendliness of the DD was higher rated for 6 questions (all p<0.05), and similar to the CD for the remaining questions (all p>0.01). Besides advantages in daily living activities with the use of the DD, also less pin tract infections were registered with this device (88% of patients with CD vs 56% with DD). Results of all questions are provided in figure 1 . Three patients who were treated with both devices (left and right knee, separately and subsequently) generally rated the DD similar to be or slightly better than the CD. Conclusion: The dedicated KJD device provides user-friendly equipment for clinicians and patients, as indicated by the shorter intervention duration and patient questionnaire outcomes, and contributes to further implementation of KJD as treatment for end-stage knee OA. References: [1]MP Jansen et al, PLOS ONE 2020 Disclosure of Interests: Mylène Jansen: None declared, Thijmen Struik Employee of: Employment by ArthroSave BV, Simon Mastbergen: None declared, Roel Custers: None declared